2017
DOI: 10.1891/1945-8959.16.2.144
|View full text |Cite
|
Sign up to set email alerts
|

Need for Cognition and Motivation Differentially Contribute to Student Performance

Abstract: The need for cognition and motivation are related to performance in school and standardized tests. In this study, 422 students completed a battery of individual difference measures and reported their scores on the American College Testing (ACT) exam, Scholastic Aptitude Test (SAT), high school grade point average (GPA), major GPA, and overall college GPA. Need for cognition was positively related to ACT and SAT scores, respectively, but not GPA. Achievement motivation was positively correlated with high school… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 32 publications
1
12
0
1
Order By: Relevance
“…It is noted that the relationship between the need for cognition and trait emotional intelligence was statistically significant whereas the relationship between the need for cognition and academic achievement was not significant. This result supported the earlier findings on the relationship between need for cognition and academic success (Neigel et al, 2017) and contradicted the study findings that there is a significant relationship between students' levels of need for cognition and their academic achievement (Akpur, 2017;Luong et al, 2017;Richardson et al, 2012;von Stumm & Ackerman, 2013). According to Elias and Loomis (2002), the contribution of need for cognition to academic achievement lends credence to the belief that if students enjoy and seek out academic tasks, it should be reflected in their academic performance.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…It is noted that the relationship between the need for cognition and trait emotional intelligence was statistically significant whereas the relationship between the need for cognition and academic achievement was not significant. This result supported the earlier findings on the relationship between need for cognition and academic success (Neigel et al, 2017) and contradicted the study findings that there is a significant relationship between students' levels of need for cognition and their academic achievement (Akpur, 2017;Luong et al, 2017;Richardson et al, 2012;von Stumm & Ackerman, 2013). According to Elias and Loomis (2002), the contribution of need for cognition to academic achievement lends credence to the belief that if students enjoy and seek out academic tasks, it should be reflected in their academic performance.…”
Section: Discussionsupporting
confidence: 66%
“…Results of this study revealed a positive relationship between academic achievement and the need for cognition as well as with other intellectual curiosity measures chosen for the study. Neigel, Behairy, and Szalma (2017) found no significant relationship between the need for cognition and students grade point average (GPA). Grass et al (2017) explored the role of the need for cognition (NFC) in academic success with a sample of 396 students from a German university.…”
Section: Studies Related To Need For Cognitionmentioning
confidence: 94%
“…Previous studies have shown that NFC acts as a positive predictor of individual academic achievement and work performance by promoting intrinsic motivation for the pursuit of knowledge and extensive cognitive processing (Grass et al, ; Luong et al, ; Neigel et al, ; Weissgerber et al, ; Wu et al, ). We extended existing research and found that NFC showed a positive correlation with creative achievement, which further confirmed the close relationship between NFC and creativity.…”
Section: Discussionmentioning
confidence: 99%
“…Creative achievement, a more ecologically valid measure of creativity, has been regarded as the sum of creative accomplishments achieved by an individual during his or her lifetime, which reflects longterm creative behaviors and may be used as a comprehensive indicator to assess individual differences in creative performance in daily life (Carson, Peterson, & Higgins, 2005;Chen et al, 2014). To our knowledge, although there is considerable empirical evidence that supports NFC as a powerful predictor of academic achievement (Bertrams & Dickhaeuser, 2009;Grass et al, 2017;Luong et al, 2017;Neigel, Behairy, & Szalma, 2017;Weissgerber, Reinhard, & Schindler, 2018) and one study showed that NFC is correlated with everyday creative behavior (Dollinger, 2003), no research has directly examined the relationship between NFC and creative achievement. Here, we tested the relationship between NFC and creative achievement in the sciences and arts and further explored whether brain flexibility associated with NFC facilitated creative achievement.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, perseverance and the willingness to invest mental effort might be other promising variables that could explain which students employ distributed practice on a self-regulated basis. In fact, females outperform males on these and other related motivational variables ( Neigel et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%